The Relationship between Breast Cancer and Vitamin D3 Deficiency in Benghazi - A. Bosafita, Fatma; F. Alramly, Hajer; K. Alsolemany, Marwa; Albarghathy, Balgess; Masoud, Wafa; Saleem., Sara (Faculty of Pharmacy, 2022)
ABSTRACT Objective: To determine the association between Vitamin D3 deficiency and breast cancer. Methods: Vitamin D deficiency was studied in 10 breast cancer patients at Benghazi Medical Center. 10 age-matched controls were also enrolled. Other parameters such as calcium and potassium were collected from the patients. The study started on 29/December/2020. Results: Mean age was 45 years old for controls and 48 years old for cases. Serum Vitamin D3 levels were lower in cases than controls. 80% of cases and 70% of controls had Vitamin D levels of less than 20 ng/ ml. Conclusion: Findings of our study cannot definitely conclude that there is an association between vitamin D deficiency and breast cancer risk. The deficiency was noticed in both groups, cases, and controls. KEY WORDS: Vitamin D3 deficiency, Brest cancer, VDR and Benghazi.